The Influencing Mechanism of Social and Cultural Adaptation for Chinese Migrant Children: A Longitudinal Intervention Study - Yu, Bingbing; Wang, Enguo (Frontiers in Psychology, 2022)
With the increasing urbanization in China, the mental health problems of migrant children have attracted widespread attention. From the perspective of social cognition, psychological capital, self-esteem and other factors are closely related to the social and cultural adaptation of the group. In order to explore the relationship among the psychological capital, self-esteem and socio-cultural adaptations of migrant children, a total of 245 Chinese migrant children were investigated with the psychological capital scale, self-esteem scale and socio-cultural adaptation scale. At the same time, 24 months group longitudinal intervention exercises was designed scientifically, the participants were provided with it continuously to enhance their psychological capital. According to the results, there were significant differences in t-test in experiment group and control group of migrant children. At the same time, there was a significant linear correlation between predictive variables’ psychological capital and self-esteem and outcome variable’s socio-cultural adaptation. In the next step of mediating effect analysis, psychological capital and self-esteem were adopted for predicting socio-cultural adaptation. The psychological capital could not only directly affect the social and cultural adaptation of migrant children, but also indirectly affect the degree of social and cultural adaptation of migrant children through changing self-esteem. The results showed that the self-esteem mediation model fitted well with the data. Furthermore, the mediation effect accounted for 17.3% in the direct effect. Longitudinal group intervention could improve the psychological capital and social and cultural adaptation of migrant children. In a word, the research was helpful to explore the influence mechanism of migrant children’s psychological capital on social and cultural adaptation, and had certain practical value in preventing and reducing the crisis caused by the social and cultural adaptation of migrant children.